Histoires de Sculpture : Giovanni Anselmo Hilla et Bernhard Becher, Christian Boltanski, Daniel Buren, Victor Burgin, Tony Cragg, Paul-Armand Gette, Gilbert & George, Hamish Fulton, Bertrand Lavier, Jean Le Gac, Sol LeWitt, Pierre Mercier, Giulio Paolini, Ane et Patrick Poirier, Françoise Vergier, Boyd Webb. - Marcadé, Bernard; Chateau des Ducs d'Épernon, Cadillac; Musée d'Art Moderne, Villeneuve d'Ascq-Nord; Atelier sur l'Herbe, Musée des Beaux-Arts, Muséum d'Histoire Naturelle, Nantes-Loire Atlantique ([S.l.] : [s.n.], 1984)
Anselmo, Giovanni ; Becher, Hilla ; Becher, Bernhard ; Boltanski, Christian ; Buren, Daniel ; Burgin, Victor ; Cragg, Tony ; Gette, Paul-Armand ; Gilbert & George ; Fulton, Hamish ; Lavier, Bertrand ; et al.
Château des Ducs d'Épernon, Cadillac-Gironde, Juin - Septembre 1984 ; Musée d'Art Moderne, Villeneuve d'Ascq-Nord, Novembre 1984 - Janvier 1985 ; Atelier sur l'Herbe, Musée des Beaux-Arts, Muséum d'Histoire Naturelle, Nantes-Loire Atlantique, Juin - Août 1985
kunstcatalogus